Regulation of B cell development and B cell signalling by CD22 and its ligands alpha 2,6-linked sialic acids - Nitschke, Lars; et al. (International Immunology, 2006)
CD22 is an inhibitory co-receptor of B cell receptor (BCR)-mediated signalling which binds specifically to glycan ligands containing alpha 2,6-linked sialic acids. This interaction modulates the CD22 activity by an unknown mechanism. Mice deficient for ST6GalI, the enzyme that generates alpha 2,6-linked sialic acids, show an immunodeficient and opposing phenotype to CD22-deficient mice. By generating mice double-deficient for this receptor/ligand pair, we analysed its influence on B cell maturation and signalling. Both ST6GalI-deficient and ST6GalI x CD22-deficient mice showed normal B cell development, but an impaired marginal zone B cell population in the spleen. Both types of mutant mice also showed a reduced population of bone marrow recirculating B cells, a defect previously detected in CD22(-/-) mice. In adoptive transfer experiments, a migration defect of wild-type B cells to the bone marrow of ST6GalI-deficient mice was found. This suggests a direct involvement of CD22 and its ligands 2,6Sia in a homing process of recirculating B cells to the bone marrow. Interestingly, defective B cell Ca2+ signalling and proliferation of ST6Gal(-/-) mice was rescued in ST6GalI x CD22-deficient mice. This points to a new mechanism of BCR signal regulation by CD22 and its ligand.
Keywords: B cell maturation; bone marrow homing; calcium signalling; proliferation; ST6GalI